Thermal evaporation and hybrid deposition of perovskite solar cells and mini-modules - Kosasih, Felix Utama (2023)
The development of perovskite photovoltaics has so far been led by solution-based coating techniques, such as spin-coating. However, there has been an increasing interest in thermal evaporation (TE) as an industrially compatible method to fabricate perovskite solar cells (PSCs). TE has several advantages compared to solution processing, including a high degree of process control, excellent film uniformity, low material consumption, conformal substrate coverage, a lack of toxic solvents, and superb device reproducibility and scalability. These benefits make TE an ideal choice to upscale lab-scale PSCs into modules. Here, we discuss three types of TE-based perovskite deposition techniques, namely 1-step TE, multistep all-TE, and multistep hybrid of TE–gas reaction and TE–solution processing. We summarize their fundamental principles and applications, firstly on small-area PSCs and then on modules. Finally, we provide our outlook on important research topics for TE PSCs, namely device interlayers, defect passivation, and device stability.